Biomechanical Pole Vault Patterns Were Associated With a Higher Proportion of Injuries - Edouard, Pascal; Sanchez, Hervé; Bourrilhon, Cyprien; Homo, Sébastien; Frère, Julien; Cassirame, Johan (Frontiers in Sports and Active Living, 2019)
Background: Pole vault is a highly demanding sport where many physical and technical requirements are engaged in performance process. Considering level of energy transferred from athlete's horizontal speed to the pole during pole bending, we can imagine that associated musculoskeletal tensions, in addition to trials accumulation, can increase the risk of (specific) injuries. Given the multiple morphological, physical and technical characteristics of vaulters and ways of pole vaulting, we can hypothesis that some patterns of pole vaults can lead to higher injury risk than others. Aim: To analyze the potential association between the biomechanical patterns of pole vault and the history of injuries. Method: We conducted a study over national-level pole vaulters including the prospective collection of pole vault biomechanical data during competition at the national elite indoor championship and youth national indoor championship (U17 and U20), associated with the retrospective collection of their injuries during the 12 preceding months through an online questionnaire. Results: Among the 88 pole vaulters participating in these championships, 62 (70.5%) accepted to participated in this study, and their pole vault biomechanical and injury data were collected. 77.4% reported having presented at least one injury during the 12 preceding months. One biomechanical parameter related to the take-off phase (lower H2, i.e., height of the grip (superior) hand from the ground when the athlete subsequently took off from the ground) and some biomechanical parameters related to the terminal phase of the run-up phase (higher Spd [i.e., speed between 10 and 5 meters to the box), SLadj (last stride adjustment), SLvar (stride length variation), tc (contact time)] were significantly associated with higher proportions of all injuries. Conclusion: Biomechanical pole vault patterns during the competition day were associated with a higher proportion of history of all injuries. Although the injury data collection was retrospective leading to recall bias risk, and do not allow determining cause-consequence relationships regarding biomechanical patterns and injury occurrence, this present study is the first to analyze potential association between the biomechanical pole vault patterns and injury occurrence, which is of great help to provide hypotheses/ideas to design future studies and to move forward into prevention measures.